Aktualisasi Nilai-Nilai Tasawuf Sebagai Solusi Problematika Sosial di Era Digital - Nurani, Fanny; Bahar, Rosid; Munir, Asep Ahmad Arsyul (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2025)
The digital era brings significant progress in human life, but also presents serious challenges in mental and social health aspects, such as increased anxiety, stress, individualism, and uncontrolled dissemination of information. This study aims to examine how Sufism values can be actualized as a solution to these problems. The method used is descriptive qualitative with a phenomenological approach and purposive sampling technique. Participants consisted of six people: three Sufism figures (practitioners and academics) and three individuals who had experienced the negative impacts of social media and found peace through the Sufism approach. Data were obtained through semi-structured interviews and in-depth documentation, then analyzed using thematic analysis techniques. The results of the study revealed five main themes: (1) the practice of dhikr and meditation as a form of digital detox that is effective in calming the mind and reducing stress, (2) the formation of a spiritual community in cyberspace that strengthens social support and religious values, (3) ethics of social media based on Sufism that emphasize politeness, empathy, and honesty, (4) the application of tawakal and self-acceptance in responding to digital social pressures, and (5) the spread of love and tranquility through spiritual content. This study provides theoretical contributions to the development of contextual Sufism studies in the digital era, as well as practical contributions to efforts to build psychosocial well-being through the integration of spiritual values in social media life.